Phylogeography and Population Genetics Analyses Reveal Evolutionary History of the Desert Resource Plant Lycium ruthenicum (Solanaceae) - Yisilam, Gulbar; Wang, Chen-Xi; Xia, Mao-Qin; Comes, Hans Peter; Li, Pan; Li, Jin; Tian, Xin-Min (Frontiers in Plant Science, 2022)
Climactic oscillations during the Quaternary played a significant role in the formation of genetic diversity and historical demography of numerous plant species in northwestern China. In this study, we used 11 simple sequence repeats derived from expressed sequence tag (EST-SSR), two chloroplast DNA (cpDNA) fragments, and ecological niche modeling (ENM) to investigate the population structure and the phylogeographic history of Lycium ruthenicum, a plant species adapted to the climate in northwestern China. We identified 20 chloroplast haplotypes of which two were dominant and widely distributed in almost all populations. The species has high haplotype diversity and low nucleotide diversity based on the cpDNA data. The EST-SSR results showed a high percentage of total genetic variation within populations. Both the cpDNA and EST-SSR results indicated no significant differentiation among populations. By combining the evidence from ENM and demographic analysis, we confirmed that both the last interglacial (LIG) and late-glacial maximum (LGM) climatic fluctuations, aridification might have substantially narrowed the distribution range of this desert species, the southern parts of the Junggar Basin, the Tarim Basin, and the eastern Pamir Plateau were the potential glacial refugia for L. ruthenicum during the late middle Pleistocene to late Pleistocene Period. During the early Holocene, the warm, and humid climate promoted its demographic expansion in northwestern China. This work may provide new insights into the mechanism of formation of plant diversity in this arid region.